Synchronous gist with gastric adenomyoma: Case report and literature review - Cardeña-Mamani, Rakel (2022)
Background: The collision of two tumors of different cell lines in the same organ is infrequent; even though, the associations described in the literature, the finding of synchronous GIST with adenomyoma draws even more attention due to its different cellular origins. Case report: We present the case of a 57-year-old female patient who underwent double wedge resection surgery and various examinations, including pathology. Conclusion: The presence of synchronous tumors, gastric GIST and gastric adenomyoma is demonstrated, despite the infrequency of this finding.